RELEVANSI PENDEKATAN NEUROPSIKOLOGIS TERHADAP KEMAMPUAN MEMBACA ANAK DISELEKSIA - Linaria Arofatul Ilmi Uswatun Khasanah; Mochamad Nursalim; Diana Rahmasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In primary schools, neuropsychology is used to understand how children learn, interact and cope with academic or social challenges, as well as to identify and support children with learning difficulties or developmental disorders. Inclusive education for children with special needs must receive educational services that are in accordance with their needs and human rights. However, it is not uncommon for schools that claim to provide inclusive education to still discriminate against children with special needs. Therefore, the role of inclusive education, social parenting and humor-based multisensory teaching that has been implemented in Indonesia and Nigeria accommodates the needs of students with various backgrounds, including children with learning difficulties, reading children with special needs dyslexia.